Condenação de carcaças bovinas por tuberculose, brucelose e cisticercose em abatedouro-frigorífico de Uberaba-MG e métodos de diagnóstico de tuberculose em carcaças - Campos, Dúnia Ibrahim (2019)
Beef is a regularly present food in Brazilian diet, with an annual per capita consumption estimated at 32.5 kg / inhabitant. The hygienic-sanitary and technological inspection of meat in slaughter establishments is an efficient and effective way of monitoring the occurrence of various diseases, identified in the post-mortem inspection of animals through the evaluation of carcasses and viscera, and removes pathogenic meat from consumption. The objectives of this work were carry out an epidemiological study on the occurrence of cysticercosis, tuberculosis and brucellosis in bovine carcasses of animals slaughtered in a slaughterhouse under federal health inspection, located in Uberaba - MG, from 2006 to 2016, in addition to correlating the methods bacteriological and histological diagnosis of post-mortem tuberculosis in condemned bovine carcasses. Slaughter data from 486,830 cattle were obtained, 457,318 (93.93%) from the region evaluated and 6.07% from other municipalities. Of the cattle studied, 3,752 (0.82%) had some of the zoonoses, of which 2,180 (58.10%) were cases of tuberculosis, 1,400 (37.31%) were cysticercosis and 172 (4.58%) were cases of brucellosis It was found there was no variation comparing the frequency of each disease in years evaluated (p> 0.05). The average frequency of tuberculosis in studied period was 0.48%, cysticercosis 0.31% and brucellosis 0.04%. In Triangulo Mineiro, the microregion of Patos de Minas was the one with the highest number of cases of tuberculosis (1.18%) and brucellosis (0.18%), the Uberaba region had the highest occurrence of cysticercosis (0.421%). These zoonotic diseases occur with low frequency in the Triângulo Mineiro and Alto Paranaíba region and in the studied period there was no variation over time in the frequency of zoonoses. In the period from March 21 to July 19, 2017, during the slaughter routine of a slaughterhouse in the city of Uberaba-MG, 11,668 cattle were slaughtered from different locations in the country. Of these, 70 carcasses were convicted - 44 (62.85%) had total conviction - grease and 26 (37.15%) partial conviction - for presenting lesions suggestive of tuberculosis. As for the location, 62.9% (44) occurred in the lungs, 17.1% (12) in lymph nodes, 15.7% (11), in the pleura and 4.3% lesions (3) were observed in the liver. In microbiological evaluation 45 (64.28%) of the samples showed the growth of colonies and these were confirmed as Mycobacterium bovis by the PCR technique. In microscopic evaluation, granulomatous lesions were the most frequent (56/70 - 80%) in all evaluated organs, with granulomatous pneumonia being the most frequent lesion (36/70 - 51.4%). In this study, 80% (56/70) of the samples were considered positive for tuberculosis in histopathological exam, 14.3% (10/70) negative and 5.7% (4/70) inconclusive. The association of complementary diagnostic methods such as bacterial isolation and histopathology are important in confirming cases of conviction of tuberculosis carcasses. The adoption of confirmatory tests can help to reduce unnecessary convictions in the industry, identify other diseases and provide information for the health decisions of official inspectors, without, however, putting food security at risk